# Charge conjugation in Dirac equation

1. Nov 5, 2012

### forhad_jnu

I need to know the mathematical argument that how the relation is true $(C^{-1})^T\gamma ^ \mu C^T = - \gamma ^{\mu T}$ .
Where $C$ is defined by $U=C \gamma^0$ ; $U$= non singular matrix and $T$= transposition.

I need to know the significance of these equation in charge conjuration .

2. Nov 6, 2012

### samalkhaiat

Start with the Dirac equation
$$( i \gamma^{\mu}\partial_{\mu} + e \gamma^{\mu}A_{\mu} - m) \psi = 0$$
Now take the complex conjugate of that and multiply from the left by some non-singular matrix $\mathcal{C}$, you then can write
$$[(i \partial_{\mu} - e A_{\mu})\ \mathcal{C}\ (\gamma^{\mu})^{*} \mathcal{C}^{-1} + m ] \ \mathcal{C}\psi = 0$$
Thus, if
$$\mathcal{C}\ (\gamma^{\mu})^{*} \mathcal{C}^{-1} = - \gamma^{\mu},$$
then the field
$$\psi_{c}\equiv \mathcal{C}\psi$$
describes another Dirac particle with opposite charge.
Now, if you write
$$\mathcal{C} = C \gamma^{0}$$
then your relation follows in the representation where
$$\gamma^{0} = ( \gamma^{0})^{T} = ( \gamma^{0})^{-1}.$$

Sam

3. Nov 7, 2012

### andrien

One can see sakurai 'advanced quantum mechanics' for an elegant derivation which describes the relationship between charge conjugated wave function and original one.

Share this great discussion with others via Reddit, Google+, Twitter, or Facebook